One Electron Reduced Square Planar Bis(benzene-1,2-dithiolato) Copper Dianionic Complex and Redox Switch by O2/HO− - Maiti, Biplab K. (2014)
The complex [Ph4P]2[Cu(bdt)2] (1red) was synthesized by the reaction of [Ph4P]2[S2MoS2CuCl] with H2bdt (bdt = benzene-1,2-dithiolate) in basic medium. 1red is highly susceptible toward dioxygen, affording the one electron oxidized diamagnetic compound [Ph4P][Cu(bdt)2] (1ox). The interconversion between these two oxidation states can be switched by addition of O2 or base (Et4NOH = tetraethylammonium hydroxide), as demonstrated by cyclic voltammetry and UV–visible and EPR spectroscopies. Thiomolybdates, in free or complex forms with copper ions, play an important role in the stability of 1red during its synthesis, since in its absence, 1ox is isolated. Both 1red and 1ox were structurally characterized by X-ray crystallography. EPR experiments showed that 1red is a Cu(II)–sulfur complex and revealed strong covalency on the copper–sulfur bonds. DFT calculations confirmed the spin density delocalization over the four sulfur atoms (76%) and copper (24%) atom, suggesting that 1red has a “thiyl radical character”. Time dependent DFT calculations identified such ligand to ligand charge transfer transitions. Accordingly, 1red is better described by the two isoelectronic structures [CuI(bdt2, 4S3–,*)]2– ↔ [CuII(bdt2, 4S4–)]2–. On thermodynamic grounds, oxidation of 1red (doublet state) leads to 1ox singlet state, [CuIII(bdt2, 4S4–)]1–.